Recent Trends in Rationally Designed Molecules as Kinase Inhibitors - Prasher, Parteek; Sharma, Mousmee; Chan, Yinghan; Singh, Sachin K.; Anand, Krishnan; Dureja, Harish; Jha, Niraj Kumar; Gupta, Gaurav; Zacconi, Flavia; Chellappan, Dinesh K.; Dua, Kamal (Current Medicinal Chemistry, 2023)
Protein kinases modulate the structure and function of proteins by adding phosphate groups to threonine, tyrosine, and serine residues. The phosphorylation process mediated by the kinases regulates several physiological processes, while their overexpression results in the development of chronic diseases, including cancer. Targeting of receptor tyrosine kinase pathways results in the inhibition of angiogenesis and cell proliferation that validates kinases as a key target in the management of aggressive cancers. As such, the identification of protein kinase inhibitors revolutionized the contemporary anticancer therapy by inducing a paradigm shift in the management of disease pathogenesis. Contemporary drug design programs focus on a broad range of kinase targets for the development of novel pharmacophores to manage the overexpression of kinases and their pathophysiology in cancer pathogenesis. In this review, we present the emerging trends in the development of rationally designed molecular inhibitors of kinases over the last five years (2016-2021) and their incipient role in the development of impending anticancer pharmaceuticals.
Keywords: RAF-kinase